MATRIX FLUX POTENTIAL BEBERAPA JENIS TANAH HOMOGEN PADA MASALAH INFILTRASI STASIONER DARI SUATU SALURAN IRIGASI TUNGGAL - Munadi Munadi; Isnani Isnani; Dian Nataria Oktaviani; Wikan Budi Utami; M. Dwi Ariwibowo (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2022)
In this paper, we study about the problem of stationary infiltration on several types of homogeneous soil from a single trapezoidal channel. A governing equation in this problem is in the form of a nonlinear differential equation and is called the Richards’ equation. The equation can be solved more easily by transforming it into a modified Helmholtz equation. In this study, Dual Reciprocity Boundary Element Method (DRBEM) was used to solve the modified Helmholtz equation numerically. Then, using the obtained solution, the numerical values of the Matric Flux Potential (MFP) for each soil type were computed and then compared.